Conjunctival Leaking Bleb after Cross- Linking using Riboflavin and UVA: A Histopathological Study - Loscos-Arenas Jordi; Tapia Gustavo; Moll-Udina Aina; Romanic Nevena; Romera Pau (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2017)
Introduction Corneal collagen crosslinking (CXL), using ultraviolet-A (UVA) radiation and ribofl avin, it is a non-invasive treatment of progressive keratoconus. As the procedure has shown a positive effect on the biomechanical of the cornea it could be a real alternative for late-onset bleb leakage in certain cases. Recent published studies [1,2], show encouraging results with this simple and non-invasive technique. Although in both series only one eye had a signifi cant intraocular pressure (IOP) increase in the fi rst set and two in the second, almost in all treated eyes the seidel test were normalized, which would support the postulate that CXL reinforces residual collagen bonding. However, in most of the eyes a slight IOP increase was observed and it is hardly attributable to the treatment because these eyes have a self-resolving tendency with a self-limiting seidel phenomena with fl uctuating visual acuity.